ГЕРОЙ И ЕГО ДОМ В РОМАНЕ ДЖЕЙМСА ДЖОЙСА ПОРТРЕТ ХУДОЖНИКА В ЮНОСТИ - Żylina, Tatiana (Acta Neophilologica, 2005)
The subject of this article is an analysis of the novel A Portrait of the Artist as a Young Man (1916) by James Joyce from a perspective of artistic space. The presented work depicts the inner and outer space of the hero’s home and house, considering the effect of the most important events of his life. It attempts to portray the changes in the relationship between the protagonist and the components of his home and house: the building, the roots, the family, to make clear why in the end he remains homeless and alone.